PHYSICAL-MATEMATICALSCIENCE MECHANICS SIMULATION CHALLENGES IN OPTIMISING THEORETICAL METAL CUTTING TASKS - Rasul V. Guseynov; Lyudmila M. Sultanova (Вестник Дагестанского государственного технического университета: Технические науки)
Abstract. Objectives In the article, problems in the optimising of machining operations, which provide end-unit production of the required quality with a minimum processing cost, are addressed. Methods Increasing the effectiveness of experimental research was achieved through the use of mathematical methods for planning experiments for optimising metal cutting tasks. The minimal processing cost model, in which the objective function is polynomial, is adopted as a criterion for the selection of optimal parameters. Results Polynomial models of the influence of angles φ, α, γ on the torque applied when cutting threads in various steels are constructed. Optimum values of the geometrical tool parameters were obtained using the criterion of minimum cutting forces during processing. The high stability of tools having optimal geometric parameters is determined. It is shown that the use of experimental planning methods allows the optimisation of cutting parameters. In optimising solutions to metal cutting problems, it is found to be expedient to use multifactor experimental planning methods and to select the cutting force as the optimisation parameter when determining tool geometry. Conclusion The joint use of geometric programming and experiment planning methods in order to optimise the parameters of cutting significantly increases the efficiency of technological metal processing approaches.